Quando as grades se abrem: crenças e intenção empreendedora de egressos de penitenciárias do estado do Ceará - Albuquerque, Larissa Cavalcante (2018)
Brazil is on the third place in the world ranking of prisional population and has hight rates of criminal recidivism (BRASIL, 2016). Faced with this panorama, entrepreneurship emerges as a possibility of resocialization and income for ex-prisoners. This research had as objective to investigate the beliefs of ex-prisoners from the state of Ceará on the intention to put a business and its motivations. With based on theory supported by the Theory of Planned Behavior (AJZEN, 1991) and the constructs of the Global Entrepreneurship Monitor (2017), the research is qualitative, exploratory and descriptive in nature. Were conducted twelve in-depth interviews with ex-prisoners who, after a period of incarceration, meet penalty in a regime open, semi-open or await trial in freedom. The data were processed through content analysis (BARDIN, 2011) and with the aid of software Atlas.ti7. The results corroborate with international research and suggest that entrepreneurship is perceived as a career opportunity for ex-prisoners and motivated, mainly, by the difficulty of getting a job. Moreover, the analysis of the interviews infers that in addition to facing difficulties own of entrepreneurship such as dealing with risk, high task burden and bureaucracy to open a business, this public also faces specific challenges resulting from their passage through the jail, such as the stigma and the prejudice of society.